Raman Spectroscopy and Aptamers for a Label-Free Approach: Diagnostic and Application Tools - Scatena, Elisa (J Healthc Eng, 2019)
Raman spectroscopy is a powerful optical technique based on the inelastic scattering of incident light to assess the chemical composition of a sample, including biological ones. Medical diagnostic applications of Raman spectroscopy are constantly increasing to provide biochemical and structural information on several specimens, being not affected by water interference, and potentially avoiding the constraint of additional labelling procedures. New strategies have been recently developed to overcome some Raman limitations related, for instance, to the need to deal with an adequate quantity of the sample to perform a reliable analysis. In this regard, the use of metallic nanoparticles, the optimization of fiber optic probes, and other approaches can actually enhance the signal intensity compared to spontaneous Raman scattering. Moreover, to further increase the potential of this investigation technique, aptamers can be considered as a valuable means, being synthetic, short, single, or double-stranded oligonucleotides (RNAs or DNAs) that fold up into unique 3D structures to specifically bind to selected molecules, even at very low concentrations, and thus allowing an early diagnosis of a possible disease. Due to the paramount relevance of the topic, this review focuses on the main Raman spectroscopy techniques combined with aptamer arrays in the label-free mode, providing an overview on different applications to support healthcare management.